Health Technology Assessment: a flexible approach? Experiences in Lombardy (Italian Journal of Public Health, 2005)
Italy is dealing with an early stage of Health Technology Assessment diffusion. In our opinion, there are atleast three important dimensions related to Health Technology Assessment (strategy, inter-organisationalrelationships and governance) that are able to affect it, at each level, systemic and operating-unit related.Although Health Technology Assessment may have originated as a centralised function conducted byfederal government agencies or other national/regional organisations, it is an increasingly decentralisedactivity. In Italy this decentralisation process is now reaching a peak because of the almost totalassignment of health responsibilities to regional authorities. Moreover, Health Technology Assessment isinterdisciplinary and it is interdependent with innovation processes. The context seems to be very complex:in our opinion a flexible approach is advisable. The following describes this new approach and theexperiences in Lombardy where various solutions have been adopted to support and improve HealthTechnology Assessment processes.
Keywords: Health Technology Assessment; innovation; clinical engineering; flexibility; Lombardy